DSP based fuzzy-neural speed tracking control of brushless DC motor - Gencer, Cetin; Saygin, Ali; Coskun, Ismail (Springer-Verlag Berlin, 2006)
In this paper, Fuzzy-Neural control architecture is applied in order to construct precise speed control of brushless DC motor (BLDC) in high performance applications. BLDC motors have been becoming popular owing to high torque density, large power to weight ratio, high efficiency, high power factor, and robustness. The proposed controller is successfully implemented in real time using a digital signal processor (DSP) board DS1104 for BLDC motor. The effectiveness of the proposed controller is verified by as well as experimental results of different dynamic operating conditions. The software of system is developed in dSPACE Control Desk.
14th Turkish Symposium on Artificial Intelligence and Neural Networks -- JUN 16-17, 2005 -- Izmir, TURKEY